Flexural strength and elastic modulus of ambient-cured blended low-calcium fly ash geopolymer concrete. (15th January 2017) - Nath, Pradip; Sarker, Prabir Kumar
Graphical abstract: Relationship of modulus of elasticity with compressive strength using existing and proposed equation. Highlights: Fly ash was blended with additives to enable ambient curing of geopolymers. Geopolymer concretes (GPC) exhibited higher flexural strength than OPC concrete. Elastic modulus of GPC is 25–30% less than that of OPC concrete of same strength. An equation is proposed to predict the modulus of elasticity of ambient cured GPC. Abstract: Fly ash geopolymer is an emerging alternative binder with low environmental impact and potential to enhance sustainability of concrete construction. Most previous works examined the properties of fly ash-based geopolymer concrete (GPC) subjected to curing at elevated temperature. To extend the use of GPC in cast-in-situ applications, this paper investigated the properties of blended low-calcium fly ash geopolymer concrete cured in ambient condition. Geopolymer concretes were produced using low-calcium fly ash with a small percentage of additive such as ground granulated blast furnace slag (GGBFS), ordinary Portland cement (OPC) or hydrated lime to enhance early age properties. Samples were cured in room environment (18–23 °C and 70 ± 10% relative humidity) until tested. The results show that, density of hardened GPC mixtures is similar to that of normal-weight OPC concrete. Inclusion of additives enhanced the mechanical strengths significantly as compared to control concrete. For similar compressive strength, flexural strength of ambient cured GPC was higher than that of OPC concrete. Modulus of elasticity of ambient cured GPC tend to be lower than that of OPC concrete of similar grade. Prediction of elastic modulus by Standards and empirical equations for OPC concrete were found not conservative for GPC. Thus, an equation for conservative prediction of elastic modulus of GPC is proposed.